2017
DOI: 10.1111/pde.13301
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of children with recurrent eczema herpeticum and response to treatment with interferon‐gamma

Abstract: Children with confirmed eczema herpeticum have evidence of impaired innate and adaptive immunity. IFN-γ did not result in dramatic improvement in either subset. Specific evaluation for IFN-γ production, function, or receptor defects may help predict response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Though a study conducted by Darji K et al concluded that gamma interferon have no role in improving EH or preventing its' relapse. 9 Till now no studies have demonstrated the evaluation of Acyclovir therapy in pediatric burn patients with EH. Although, its use has been described in children hospitalized with EH.…”
Section: Discussionmentioning
confidence: 99%
“…Though a study conducted by Darji K et al concluded that gamma interferon have no role in improving EH or preventing its' relapse. 9 Till now no studies have demonstrated the evaluation of Acyclovir therapy in pediatric burn patients with EH. Although, its use has been described in children hospitalized with EH.…”
Section: Discussionmentioning
confidence: 99%
“…Prompt treatment with systematic antiviral medication can prevent or lessen complications [5]. Acyclovir is the gold standard therapy, although immunomodulatory treatments have also been considered with controversial results [6]. According to Aronson et al [7], antibiotics do not really affect the prognosis of this entity, although the prophylactic use of antibiotics could prevent certain secondary bacterial infections.…”
Section: Discussionmentioning
confidence: 99%
“…In children, following fever and lymphadenopathy, the oral manifestations of HSV-1 infection are gingivostomatitis and vesiculo-ulcerative eruption on the perioral skin, vermillion border, and intra-oral mucosal surface. The vesicles, after rupture, are painful as they are left to heal without scarring [62]. The herpes simplex virus migrates in later stages to the trigeminal ganglion, accounting for 15% to 30% of cases, and is affected by the reactivation of secondary herpes simplex lesions in early adulthood due to stress or infection.…”
Section: Herpes Simplex Virusmentioning
confidence: 99%